PENYIRAMAN MEDIA TANAM SAMBUNG PUCUK KOPI (Coffea sp) PADA BERBAGAI KONSENTRASI PGPR - Kafrawi kafrawi; Raihan Arif; Andi Muh Siddiq A Kahrir; Nildayanti Nildayanti; Zahraeni Kumalawati; Suriansyah Suriansyah (Agroplantae: Jurnal Ilmiah Terapan Budidaya dan Pengelolaan Tanaman Pertanian dan Perkebunan, 2020)
The aim of this experiment was to determine the best PGPR concentration to support coffee shoot grafting. The experiment was carried out in the form of a completely randomized design (CRD) consisting of 4 treatments, namely without PGPR or control K0 (concentration 0 ml L-1 water), K1: 10 ml, L-1 water, K2: 20 ml L-1 water, and K3: 30 ml. L-1 water is given to each polybag. Each treatment had 4 replications so that there were 16 experimental units. The results showed that giving PGPR with a concentration of 30 ml L-1 of water to shoot grafts gave the best results on shoot height and shoot diameter growth. Whereas at a concentration of 10 ml.L-1 water gave the best effect on the increase in the number of leaves of coffee shoot grafting seeds.